Kajian Alternatif Proyeksi Jaringan Jalan Hutan untuk Perencanaan Pemanenan Kayu di PT Inhutani I Labanan, Propinsi Jawa Barat - Muamar Kadafin; Alfian Pujian Hadi; Akbar Al Imam (Otus Edu Journal Prodi Tadris IPA Biologi UIN Mataram, 2024)
Forests are one of the natural resources that can be utilized in the form of both wood and non-wood forest products. Harvesting carried out to extract wood results in negative impacts such as soil damage and damage to standing stands. The negative impacts of wood harvesting can be reduced by planning in advance, such as creating a forest road network. The research was carried out in the mahogany room, utilization division, forest management department, while the assessment of the forest road network used the case study of PT Inhutani I Lebanan. The aim of the research is to examine the planning and selection of the best alternative forest road network for harvesting wood using multi-criteria decision making techniques. The research will be carried out in March 2023. The research stage begins with sketching the road network; assess road networks using economic, ecological and technical criteria; as well as conducting literature studies from various sources. The research results show that there are six alternative forest road networks for harvesting wood. This is based on forest road network assessment parameters that the best alternative road network in the PT Inhutani I Labanan road scheme is the 6th road network alternative. Sustainable management of forest resources can be achieved through a well-planned road network. The highest total utility value (rank 1) is found on the 6th road network which is the best alternative forest road network to be implemented at PT Inhutani Labanan I both in terms of technical aspects, ecological aspects and economic aspects.